Uji Beban dan Analisis Lendutan Model Pelat Fleksibel yang Didukung Tiang-Tiang pada Tanah Pasir - Hartono, Edi (Jurnal Semesta Teknika, 2013)
Sand commonly has a good bearing capacity. Problems may occur when sand has low density and thick deposit. Flexible plate foundation may be used in this soil but plate deflection may be still high. To reduce deflection and improving soil density, piles were used to support the plate. Installing piles made foundation system stiffer. The objectives of this study areÂ  to studies about behavior of plates and plate with a pile of sand on the ground, influence of plate thickness , pile length and spacing of the pole deflection, and the influence of the bond between the plate and the deflection of the pile .In this study is used test box of 1.2 m depth, 1.2 m width, 1.2 m length, and 1.0 m depth filled out with sand. Plate models were made from plexiglas of rectangular and square geometry. Piles were of steel pipesof 2.5cm diameter. Some parameters were as follows : plate thickness, plate geometry, pile length (L), pile spacing (s), bounding between plate and pile (fix or free), âpiledâ and freestanding foundation, and base pile enlargement. The behavior of the plateswere observed under loading (point load). The result shows that plate deflections were affected by the method of pile installation, plate thickness and pile length. For a ticker plate, contact surface between plate and soil was wider. For the 40cmx10cm plates with fix end pile, deflectionswere founf to reduced up to 70% compared with free end pile. The âpiled foundationâ on 40cmx10cm plates, L=20cm, s=4d, deflections were reduced 83,63% compared with free standing foundation.